RABIES EXPOSURE PROTOCOL UPDATE, EMERGENCY SUPPORT FUNCTION 11 RESOURCE DETERMINATION, AND MASS TUBERCULOSIS SCREENING FOR JOHNSON COUNTY, KANSAS - Lewis, Christopher (My University, 2015)
The modernized world has been able to reduce the prevalence of rabies through increased vaccination of pets, public education, and bait vaccination programs targeting wild animals. Though not the public health issue it once was, human rabies infections are still a concern and possible exposures are monitored closely in Johnson County, Kansas. The Johnson County Department of Health and Environment determined there was a need to revise the current rabies exposure protocols to assist health officers during their investigations and to encourage the completion and proper submission of rabies exposure forms. Protecting people after a man-made or natural disaster or emergency has always been a concern within the emergency management community, but the need to account for animals during these events has become a major focus. After recent instances of people losing their lives rather than leave their pets during a disaster, planning for humans and animals is now a requirement in emergency management. But before this planning can begin, the determination of available resources is critical in order to convey what must be procured. Johnson County officials found their resource database was outdated and were anxious to remedy that problem. Tuberculosis is an infectious disease that, like rabies, is not prevalent in developed countries but is still closely monitored. Near the end of the Field Experience, a Johnson County high school student was diagnosed with active tuberculosis. The Johnson County Department of Health and Environment thoroughly investigated this incident, including a mass screening at the student’s school; activities included planning, performance, and review of the screening event. Activities applicable to the core and emphasis area competency requirements for the Master of Public Health Infectious Diseases/Zoonoses program are described. Challenges encountered during the Field Experience are listed and described. The advantages and disadvantages of having a veterinarian conduct the Rabies and ESF 11 Projects is discussed. Key concepts of public health practices encountered during the Field Experience are also examined. Important documents produced or utilized during the Field Experience are included in appendices to the report.
Keywords: Rabies; Rabies exposure; Emergency support function 11; Disaster resources; Tuberculosis; Mass screening; Public Health (0573)